Strategi Pengembangan Usaha Jamur Tiram Putih di Desa Simbang Kecamatan Simbang Kabupaten Maros : (Studi Kasus Kelompok Wanita Tani Simbang Sejahtera) - Amir, Nurjannah; Yunus, Awaluddin; Kadir, Muh. Ichwan; Syamsinar, S; Hardiani, A. Susilawaty (Journal Galung Tropika, 2023)
The sale of mushrooms depends on demand in the village as well as demand from outside the region, such as the Makassar area, minimal capital and lack of production facilities that can support production. This research was carried out in Simbang Village, Simbang District, Maros Regency in October-November 2022. The purpose of this study is to find out internal and external factors and to find out how the oyster mushroom business development strategy of the Simbang Sejahtera Peasant Women's Group, Simbang Village, Simbang District, Maros Regency. The research methods used were observation, interviews and documentation by taking 25 people as respondents. The data used are primary data and secondary data. The data analysis used is a SWOT analysis. From the results of the analysis internal actors, namely marketing, human resources, production and operations, and finance. External factors are economic, climate, demographic, social, governmental, customer, supplier, and industry. the results of the SWOT analysis and QSPM and AHP there are 4 alternative strategies based on the location of the oyster mushroom business in quadrant I, which can be implemented, namely optimizing production to increase profits, being consistent in maintaining the quality of oyster mushrooms, expanding market reach online, and making processed oyster mushroom products in accordance with changes in consumer tastes who apply a healthy lifestyle, and can integrate alternative strategies to optimize the performance of the oyster mushroom business.